Web services platforms emerge SOA goes mainstream. - Shaffer, Dave
J2EE application servers enabled mainstream developers to build sophisticated multitiered Web applications that use mature standards and any of several commercial and open source application server platforms. A similar pattern has now emerged with the maturation of standard platforms for enabling service-oriented architectures (SOA) through Web services. These Web services platforms provide the same mainstream developer community with design patterns for implementing composite applications that leverage adapters, integration, transformation, business process management and Web services. This article examines the key requirements for an effective Web services platform, related standards and what impact this is having on developers and enterprise IT.